2018
DOI: 10.1186/s41155-018-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship between adverse childhood experiences, life events, and executive function among college students in China

Abstract: Objective: The aim of this study was to investigate the effects of adverse childhood experiences and life events on the inhibitory control ability, cognitive flexibility, and working memory of college students. Methods: The study involved testing the participants using the Adverse Childhood Experiences (ACEs) Questionnaire, the Adolescent Life Events Scale (Adolescent Self-rating Life Events Checklist, ASLEC), and the program of executive functions designed by E-prime software. Results: The incidence rate of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…positively or negatively) executive functions (EFs) was the focus of interdisciplinary studies. In traumatic stress research, the focus was mostly on the impact of early childhood trauma(e.g., DePrince et al, 2009;Ji & Wang, 2018;Majer et al, 2010;Mirabolfathi et al, 2020;Moreno-Manso et al, 2020;Mothes et al, 2015;Op den Kelder et al, 2018;Spies et al, 2016). However, a recent study found that executive exposure to threats, regardless of trauma types, impaired executive functions for those only who negatively appraise such threats (Newman et al, 2020).…”
mentioning
confidence: 99%
“…positively or negatively) executive functions (EFs) was the focus of interdisciplinary studies. In traumatic stress research, the focus was mostly on the impact of early childhood trauma(e.g., DePrince et al, 2009;Ji & Wang, 2018;Majer et al, 2010;Mirabolfathi et al, 2020;Moreno-Manso et al, 2020;Mothes et al, 2015;Op den Kelder et al, 2018;Spies et al, 2016). However, a recent study found that executive exposure to threats, regardless of trauma types, impaired executive functions for those only who negatively appraise such threats (Newman et al, 2020).…”
mentioning
confidence: 99%
“…The aspect that concerns us here is that of executive functioning, or, simply, executive function. Executive function includes higher order processes-working memory, inhibitory control, and cognitive flexibility-that enable complex decision-making goal-directed behaviour, and the development of key cognitive and socioemotional skills (Ibrahimet al, 2017;Ji & Wang, 2018;Logue & Gould, 2014). Executive function refers, essentially, to the psychological processes that consciously control thought and action (Zelazo & Müller, 2011).…”
Section: Re-centring Cognition In Explanations Of Teaching and Learningmentioning
confidence: 99%
“…It has come to underline the importance of understanding executive function better. The ability to adapt through goal-directed behaviour and regulation of reflexive reactions is based on executive function (Ji & Wang, 2018;Logue & Gould, 2014).…”
Section: Re-centring Cognition In Explanations Of Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of exposure to stressors and traumatic events and their mental health consequences on executive functions (EFs) attracted scholars' attention. However, the focus was mostly on the impact of early childhood trauma(e.g., DePrince et al, 2009;Ji & Wang, 2018;Majer et al, 2010;Mirabolfathi et al, 2020;Moreno-Manso et al, 2020;Mothes et al, 2015;Op den Kelder et al, 2018;Spies et al, 2016). Other general and specific trauma types did not attract as much attention.…”
mentioning
confidence: 98%